2020
DOI: 10.1186/s12882-020-02104-0
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for severe acute kidney injury among patients with rhabdomyolysis

Abstract: Background Acute kidney injury (AKI) is a life-threatening complication of rhabdomyolysis (RM). The aim of the present study was to assess patients at high risk for the occurrence of severe AKI defined as stage II or III of KDIGO classification and in-hospital mortality of AKI following RM. Methods We performed a retrospective study of patients with creatine kinase levels > 1000 U/L, who were admitted to the West China Hospital of Sichuan Univer… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 38 publications
1
11
1
Order By: Relevance
“…A recent report showed that serum uric acid was an independent predictor of AKI in patients with COVID-19 [32]. Platelet count and white blood cell count were two biomarkers for AKI, and low level of platelet count and high level of white blood cell count could increase risk of AKI [33][34][35][36] which was consistent with our ndings.…”
Section: Discussionsupporting
confidence: 91%
“…A recent report showed that serum uric acid was an independent predictor of AKI in patients with COVID-19 [32]. Platelet count and white blood cell count were two biomarkers for AKI, and low level of platelet count and high level of white blood cell count could increase risk of AKI [33][34][35][36] which was consistent with our ndings.…”
Section: Discussionsupporting
confidence: 91%
“…RM is a common severe clinical presentation with complicated etiologies. The causes of RM were different among various studies [4,8,20]. In our present cohort, the common causes were trauma, heat stroke, and vascular ischemia.…”
Section: Discussioncontrasting
confidence: 52%
“…Acute kidney injury (AKI) is the most common and severe complication of RM, occurred in 20%-60% of patients with RM. And, for RM related AKI patients, the mortality rate was signi cantly increased and was reported to be as high as 60% [3,4]. The elevated circulation myoglobin, which could accelerate kidney injury by promoting vasoconstriction, blocking renal tubules, causing oxidative stress lipid peroxidation, and inducing in ammation, is considered to be the most important pathogenesis of RM related AKI [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Certain risk factors are associated with increased mortality rate, including patients with hypertension, low levels of high-level data link control (HDLC), elevated white blood cells, age >60 years, hypertriglyceridemia, and hyperphosphatemia [13]. The recommended rate of crystalloid fluid initiation is at a rate of 1.5L per hour to maintain an adequate urine output of approximately 200-300 cc per hour [2].…”
Section: Discussionmentioning
confidence: 99%